2007
DOI: 10.1007/s11199-007-9233-1
|View full text |Cite
|
Sign up to set email alerts
|

College Alcohol Use and the Embodiment of Hegemonic Masculinity among European American Men

Abstract: This article concerns alcohol use as it pertains to the construction of White masculinity through an analysis of students' accounts. Seventy-eight face-to-face interviews were conducted with volunteer female and male, African American, European American, heterosexual and homosexual students at a mid-sized university. Results suggest that the meaning of public drinking is to express a form of masculinity. In students' gendered descriptions of their own and peers' drinking behavior, alcohol use among White men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
234
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 56 publications
(58 reference statements)
14
234
0
2
Order By: Relevance
“…This is consistent with literature that shows men frequently use alcohol in their homosocial bonding (Peralta, 2007;West, 2001), and this is particularly true in England.…”
Section: Alcohol: Influence or Excuse?supporting
confidence: 91%
“…This is consistent with literature that shows men frequently use alcohol in their homosocial bonding (Peralta, 2007;West, 2001), and this is particularly true in England.…”
Section: Alcohol: Influence or Excuse?supporting
confidence: 91%
“…This difference might be explained by the gender role associated with certain types of behavior. For example, research has shown that masculinity is related to health behavior such as regular exercise [47] smoking, and drinking [48,49]. Therefore, men might be more likely to engage in such behavior to emphasize their masculine gender role.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, men may report that the ability to consume large amounts of alcohol without fainting or vomiting, is equated with masculinity (Peralta, 2007), demonstrating the extent to which drinking is a gendered activity.…”
Section: Gender and Healthmentioning
confidence: 99%